(untitled) (Journal of International Studies, 2020)
Since the early 1990s, Singapore-India relations have progressed rapidly in most fields. In the economic realm, Singapore companies have invested massively in the Indian telecommunications industry. Bilateral trade rose 40% from 2004 to 2005 and increased further following the conclusion of the Comprehensive Economic Cooperation Agreement between the two states in 2005. 1 In 2006, bilateral trade jumped 20% to S20 billion.2 Defense relations, which have also been enhanced, are epitomized by the signing of a Defense Cooperation Agreement (DCA) in October 2003. Among other agreements, the DCA gave the Republic of Singapore Armed Forces (RSAP) access to Indian training facilities.3 Although the progress in Singapore-India economic relations has been analyzed in a many studies, analyses of security and defense cooperation have been undertaken primarily in the broader context of India’s relations with ASEAN.4 In the current study, we analyze Singapore-India defense relations in the post-Cold War era. The study begins by examining the defense policies of Singapore and India, especially the transformation from mutual suspicion towards cooperation with the onset of the postCold War era. Various areas of defense and security cooperation will be highlighted. The implications of the rise in defense cooperation between the two countries and the way in which it impacts regional security will be also discussed. Although defense relations between both states have improved rapidly since 1993, new avenues of cooperation are also being assessed, including research and development [R&D] and humanitarian operations. Pitfalls along the path to closer cooperation are evidenced by China’s apprehension over India’s increasing influence in Southeast Asia. In addition, potential conflicts between India and Pakistan could place Singapore in an awkward position if the strategic partnership of Singapore and India continues to strengthen.